Optimising pharmacy processes in medication delivery service through digitalisation and automation - Kian Hong Hong Ng; Wen Jun Tiew; Yook Ting, Amanda Woo; Wei Xiong, Nathaniel Lim; Tou Teik, George Lim; Arleen Susan Baskaran (BMJ Open Quality)
The rapid expansion of medication delivery service (MDS) during COVID-19 created many new roles in the pharmacy which are manpower intensive and not sustainable as pharmacy resumes counter collection services. To keep MDS operations sustainable, we identified the need to streamline and automate processes which are manual and repetitive. We seek to determine if the Plan, Do, Study, Act (PDSA) cycles would effectively reduce the man-hours required for the MDS over two phases in 1 year. Phase 1 involved digitalisation of order taking and automation of the data entry process. Phase 2 involved automating the order generation and accounting process to replicate the patient information matching task which was performed manually during bagging and dispatch of delivery orders. The baseline period for this study was from December 2020 to January 2021. The results following implementation of PDSA cycles in the respective phases were collected between January 2021 to June 2021 and July 2021 to December 2021. The average time taken for data entry per delivery order reduced from a range of 0.5 to 2.15 min to 0.08 to 0.1 min depending on the ordering method (p<0.05). The average time taken for bagging and dispatch per delivery order shortened from 2.7 min to 0.28 min (p<0.05). The improvements were sustained and cumulatively contributed to 11.8-man-hour savings. The impact of the interventions was discussed. As MDS gains prominence as an important alternative for medication collection due to its rapid expansion due to COVID-19, it is crucial for the pharmacy to expand its capacity and information technology capabilities to cope with higher workload from both MDS and walk-in patients.